2020
DOI: 10.1101/2020.08.06.239517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Disruption of WASHC4 Drives Endo-lysosomal Dysfunction and Cognitive-Movement Impairments in Mice and Humans

Abstract: Mutation of the WASH complex subunit, SWIP, is implicated in human intellectual disability, but the cellular etiology of this association is unknown. We identify the neuronal WASH complex proteome, revealing a network of endosomal proteins. To uncover how dysfunction of endosomal SWIP leads to disease, we generate a mouse model of the human WASHC4c.3056C>G mutation. Quantitative spatial proteomics analysis of SWIPP1019R mouse brain reveals that this mutation destabilizes the WASH complex and uncovers signif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 126 publications
(224 reference statements)
0
6
0
Order By: Relevance
“…SWIP is an understudied component of the WASH complex with mostly helical arrangement and few structural domains that could provide insights into its function. Intriguingly, the P1019R substitution in SWIP is implicated in one form of autosomal recessive intellectual disability (Ropers et al, 2011), and the mutation leads to decreased affinity of SWIP to other WASH complex subunits (Courtland et al, 2021). Understanding the membrane-binding role of SWIP in the pathogenesis of this form of intellectual disability merits further research.…”
Section: Discussionmentioning
confidence: 99%
“…SWIP is an understudied component of the WASH complex with mostly helical arrangement and few structural domains that could provide insights into its function. Intriguingly, the P1019R substitution in SWIP is implicated in one form of autosomal recessive intellectual disability (Ropers et al, 2011), and the mutation leads to decreased affinity of SWIP to other WASH complex subunits (Courtland et al, 2021). Understanding the membrane-binding role of SWIP in the pathogenesis of this form of intellectual disability merits further research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that KO of WASH, Strumpellin and the retromer protein subunit VPS26a all individually result in embryonic lethality (Muhammad et al, 2008;Piotrowski et al, 2013;Tyrrell et al, 2016), though VPS26b-KO mice survived despite displaying sortillin trafficking defects (Kim et al, 2010). Genetic disruption arising from SWIP P1019R mutation resulted in significant and progressive motor deficits in mice that were similar to movement deficits observed in humans (Courtland et al, 2021). Despite being a component of the WASH protein complex, whether FAM21 mutations are associated with any known human diseases remains unknown, so our investigation of the function of FAM21 in vivo is critical to understanding if FAM21 plays a role in disease prevention.…”
Section: Introductionmentioning
confidence: 81%
“…In the current study, 104 proteins were found to be differentially expressed in male F. occidentalis infected with TSWV, and the predicted functions of these proteins were related to the nervous, endocrine, circulatory, and reproductive systems. Among the 104 proteins, seven immune‐related proteins were significantly up‐regulated, including a lysosomal‐associated organelle subunit WASH complex subunit 4, which may be involved in humoral immunity 44 . Ctenidin‐3‐like peptides rich in antimicrobial glycine and heat shock 70 kDa Protein II‐like proteins may contribute to defense against alien organisms, as well as biological and abiotic stressors 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the 104 proteins, seven immune-related proteins were significantly up-regulated, including a lysosomal-associated organelle subunit WASH complex subunit 4, which may be involved in humoral immunity. 44 Ctenidin-3-like peptides rich in antimicrobial glycine and heat shock 70 kDa Protein II-like proteins may contribute to defense against alien organisms, as well as biological and abiotic stressors. 45,46 Interestingly, 14 protein genes, including those encoding actin and E3 ubiquitin ligase (related to spermatogenesis), calcium signal transduction protein, serine/threonine protein kinase, and FSCB-like protein (related to capacitation of sperm) were significantly down-regulated in males exposed to TSWV.…”
Section: Discussionmentioning
confidence: 99%